Radio-protective effect of vitamin E on spermatogenesis in mice exposed to γ-irradiation: A flow cytometric study - C. Songthaveesin (2018)
Aim: To investigate the effect of vitamin E on the radioprotection of spermatogenesis and chromatin condensation of spermatozoa during passage through the epididymis in mice exposed to irradiation. Methods: Adult outbred male ICR mice were orally administered natural vitamin E (VE, D-α-tocopheryl acetate) at 400 IU/kg for 7 days before exposure to 1 Gy of γ-irradiation. The animals were sacrificed at day 1, 7, 14, 21, 28, 35 and 70 post-irradiation (IR) and the percentage of testicular germ cells and epididymal sperm chromatin condensation was analyzed using flow cytometry. Results: Serum D-α-tocopheryl acetate levels were 47.4 ± 3.2 μg/dL in the treated group, yet it could not be detected in the control group. The testicular weight of irradiated mice pretreated with VE+IR was significantly (P<0.05) higher than that of those without VE treatment (IR) at day 14 and 21 post-irradiation. The percentage of primary spermatocytes (4C) in the VE+IR group was comparable to the controls but significantly (P<0.05) higher than those in the IR group from day 7 to 35 post-irradiation. The percentage of round spermatids (1C) in the VE+IR group was also significantly (P<0.05) higher than those in the IR group at day 28 post-irradiation. The primary spermatocytes : spermatogonia ratio in the IR group was significantly (P<0.05) declined at day 7 to 35 post-irradiation when compared to the VE+IR and control groups. The round spermatid : spermatogonia ratio in the VE+IR group was significantly (P<0.05) higher than that of the IR group at day 14 and 28 post-irradiation. The chromatin condensation of epididymal spermatozoa measured by propidium iodide uptake was not affected by 1 Gy of γ-irradiation. Conclusion: The administration of VE prior to irradiation protects spermatogenic cells from radiation. © 2004, Asian Journal of Andrology.